Restay Decision Influenced by Social Media and e-WOM Intervened by Satisfaction at Marinsow Homestay - Matu, Ivanry; Pradiani, Theresia; Fathorrahman, Fathorrahman (Indonesian Journal of Multidisciplinary Science, 2023)
Tourism has become a leading sector in driving economic growth. Repeat stays are critical for the continuity and economic growth of homestay businesses in the Likupang Super Priority Tourism Destination area. This study aims to examine the influence of social media and electronic word of mouth (e-WOM) on repeat stay decisions, mediated by tourist satisfaction. The study involved 120 respondents who had stayed at Marinsow Homestay Likupang, North Minahasa, at least twice. Data were collected through questionnaires and analyzed using path analysis. The results showed that social media and e-WOM have a positive and significant effect on tourist satisfaction, tourist satisfaction has a positive and significant effect on repeat stay decisions, social media has a significant effect on repeat stay decisions, and e-WOM has a positive and significant effect on repeat stay decisions for tourists staying in homestays.